Quantifying ion desolvation effects on capacitances of nanoporous electrodes with liquid electrolytes. (31st August 2021) - Qing, Leying; Long, Ting; Yu, Hongping; Li, Yu; Tang, Weiqiang; Bao, Bo; Zhao, Shuangliang
Graphical abstract: Microporous electrode →confinement-dependent solvation diameter. Upon coarse-grained molecular model, the important contribution of ion desolvation to the capacitance is evaluated. Highlights: A multiscale molecular approach is proposed to unravel the confinement-dependent solvation idiameter. This approach is coupled with the combination of the simple and molecular versions of classical density functional theory. This approach is a feasible tool for predicting the capacitance of microporous electrodes. Abstract: Understanding ion desolvation effect in microporous electrodes is helpful towards high-efficient energy storage. Herein, we evaluate the contribution of ion desolvation to the electrochemical performance of microporous electrodes with a proposed multiscale approach. By combining the molecular density functional theory (DFT) with the simple DFT, we determine the ion solvation diameters in confined liquid acetonitrile, and then predict the capacitances of microporous electrodes involving acetonitrile-based electrolytes through a solvation-diameter-dependent coarse-grained model. We find that the ion solvation diameter displays an oscillatory decline as decreasing the pore size of nanoslit. Integrating this decline relation with the pore size distributions of microporous electrodes we show that the capacitances of practical electrodes can be quantitatively predicted in comparison with experimental measurements. This work not only provides a promising multiscale approach for investigating the properties of confined electrolytes, but also casts insights for the design and preparation of high-performance supercapacitors.